2003
DOI: 10.1016/s0920-9964(02)00289-x
|View full text |Cite
|
Sign up to set email alerts
|

Associative memory in chronic schizophrenia: a computational model

Abstract: We developed a computer model to simulate associative memory recall of patients with chronic schizophrenia. Model inputs consisted of words derived from normative data that differed in terms of connectivity and network size, with the former quantitatively represented by parametric weights and the latter by the specific number of word associates that formed a particular network. Previous behavioral studies of normal subjects indicated better recall for words of high connectivity-small network (HCSN), followed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1

Year Published

2006
2006
2008
2008

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 19 publications
0
9
1
Order By: Relevance
“…This effect in patients may be weakened, perhaps due to an associational bias that leads to restricted semantic integration and contributes to disturbed thinking. (e.g., Chapman and Chapman, 1973;Nestor et al, 1998;Han et al, 2003). However, the current findings are limited, demonstrated as statistically significant on the basis of within-but not between-group analyses.…”
Section: Discussioncontrasting
confidence: 63%
“…This effect in patients may be weakened, perhaps due to an associational bias that leads to restricted semantic integration and contributes to disturbed thinking. (e.g., Chapman and Chapman, 1973;Nestor et al, 1998;Han et al, 2003). However, the current findings are limited, demonstrated as statistically significant on the basis of within-but not between-group analyses.…”
Section: Discussioncontrasting
confidence: 63%
“…These fMRI data suggested that the schizophrenic group did not process word connectivity relationships in the same manner as their demographically-matched control counterparts; showing a relatively less robust HLU regression activation pattern among language-specific left temporal and frontal regions. Given the strong empirical support for word connectivity as a parameter sensitive to the spreading of activation through lexical-semantic association networks broadly distributed across these areas (Nelson et al, 1993;Nestor et al, 1998;Han et al, 2003;Wible et al, in press), the current results suggest either a disease-related disturbance in lexical-semantic network organization, a disruption of activation through interrelated concepts, or a combination of these possibilities. Warrington (1975) presented a hierarchical model of semantic knowledge and suggested that subordinate categorical information may be more sensitive to damage than superordinate information.…”
Section: Discussionmentioning
confidence: 63%
“…Employing an empirically-derived database of word associations (Nelson et al, 1999), we were able to successfully simulate the word recall responses for both control and schizophrenic subjects. Furthermore, we were able to show evidence for an orderly degrading of network associational threads accounting for the behavioral response over and above random activation and disorganization (Han et al, 2003).…”
Section: Introductionmentioning
confidence: 74%
See 2 more Smart Citations